Mind, State and Society Social History of Psychiatry and Mental Health in Britain 1960-2010 - Ikkos, George; Bouras, Nick (Medicine, 2021)
Mind, State and Society examines reforms in psychiatry and mental health care in Britain during 1960-2010 and their relation to society. A truly multidisciplinary account, it will appeal to psychiatrists, mental health professionals, policymakers, social scientists, historians and activists. It is also available as Open Access on Cambridge Core.